PERENCANAAN TEKNIS SISTEM PENYALIRAN TAMBANG BATUBARA PADA PT. NAN RIANG KABUPATEN BATANGHARI PROVINSI JAMBI - Glory Hutagalung; Yulius G. Pangkung (Jurusan Teknik Pertambangan Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2018)
PT. Nan Riang is a coal mining company located in Muara Tembesi District, Batanghari Regency, Jambi Province. PT. Nan Riang applied open pit system in its operation, in which Stripe Mine was considerably implemented as the main method. The utilisation of this method would form pits, so that, during rainy days, the water could potentially be stagnant in front. The catchment areas are divided into 6 sections; the 1st catchment area was 0.00929 km2, the 2nd catchment area was 0.06017 km2, the 3rd catchment area was 0.03256 km2, the 4th catchment area was 0.03960 km2, the 5th catchment area was 0.08065 km2, and the 6th catchment area was 0.02596 km2. From the calculation of drainage dimensions, it was highlighted that the water level was approximately 0.26 m, width of drainage was about 0.39 m, width of drainage surface was 0.78 m, wet circumference was about 0.73 m, the depth of was 1.07 m, and length of side was 1.19 m. The pump that is set for the drainage was LCC-H 50-230, with the pumping capacity of 3,405 m3/ hour. These pumps have Total Head of 90 m, with the impeller rotation of 3710 rpm. The amount of water entering the settling pond was 15.80336 m3/ second, with the settling widht of 29.71 m2 pond. Regarding the dimensions of settling pond, in which water could be gathered as calculated, therefore settling pond should be set at 10 m in length, 4 m in width and 2 m in height, with the volume of 237.64451 m3.